Essentials of strategic management - Rodgers, Dustin
"The branch of management that involves formulation and implementation of goals is known as strategic management. It focuses on evaluating the available resources and assessing the internal and external environments in which the company operates. It involves identifying a company's objective and forming plans and policies to achieve those objectives. It is also concerned with the allocation of resources to achieve the goals of the organization. This discipline includes two processes. These are formulation and implementation. It uses various frameworks and concepts such as experience curve, industry structure and profitability, SWOT analysis, corporate strategy and portfolio theory and generic competitive strategies. Globalization, self-service, sustainability and internet and information availability are some of the strategic themes on which this discipline is based. This book is a compilation of chapters that discuss the most vital concepts in the field of strategic management. It presents this complex subject in the most comprehensible and easy to understand language. For someone with an interest and eye for detail, this book covers the most significant topics related to this discipline."--